Before Auschwitz : Jewish prisoners in the prewar concentration camps - Wünschmann, Kim (Harvard University Press, 2015)
In the beginning there was violence: "protective custody" and arrests of Jews, 1933-1934 -- Inside the early concentration camps: abuse, isolation, and murder of Jews, 1933-1934 -- Her transport to the concentration camp has been ordered: arrests and imprisonment of Jewish women, 1933-1939 -- Cementing the enemy category: Jews in the evolving SS concentrations camp system, 1935-1938 -- Instruments of mass persecution: the concentration camps and anti-Jewish policy in 1938 -- The calm before the storm?: Jews in the concentration camps in 1939